Factors of job satisfaction among workers exposed to occupational noise - Rasdi, Irniza; Mohd Zin, Noraini; Syed Ismail, Sharifah Norkhadijah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Noise was evident to reduce job satisfaction among workers which will negative impacts to workers including increase job turnover, decrease motivation and increased number of accidents. This study aims to explore job satisfaction and its risk factors among workers working in a noisy workplace. Method: The study design was cross-sectional study which involved 167 workers in a cable manufacturing factory selected by simple random sampling. MSQ was used to assess employee’s satisfaction with their job on seven facets and sound level meter was used to measure workplace noise level. Results: All respondents were exposed to noise above permissible exposure limit. Most workers (49%) were moderately satisfied with their work. Factors that were rated as lowest level of satisfaction were work itself (the ability to work alone) (40%) and the way company system policies are implemented (40%). Factors with the highest level of satisfaction were their freedom to implement their judgement (responsibility) (51%) and the supervision quality of their superiors (51%). The most dominant facet predicting total satisfaction level was recognition followed by advancement and company policy and administration. All variables in socio-demographical and job characteristics were not significantly associated with their level of job satisfaction except noise. Noise was significant in predicting one facet of job satisfaction which was physical work condition. Conclusion: Overall, the average level of job satisfaction among respondents were moderate and they were exposed to occupational noise which was the only significant study variable correlated with their job satisfaction.